Nostalgic card games as a dementia prevention therapy in the elderly - Cahyani, Ganesa Gita Ayu; Kartinah, Kartinah; Rohman, Muhammad Fathoni (Institute of Computer Science (IOCS), 2025)
PAKARNOS is a cognitive training effort to prevent dementia in the elderly by enhancing their memory through storytelling based on images. This nostalgia card game utilizes reminiscence therapy, encouraging elderly individuals to recall past events, relax their minds, and alter their response to dementia. Dementia is a clinical syndrome characterized by a decline in intellectual function, memory impairment, and cognitive deterioration, which can disrupt daily life and affect the elderly's bio-psycho-social-spiritual well-being. PAKARNOS involves showing old pictures to elderly participants, with a facilitator providing keywords to stimulate memory recall and storytelling. This method helps sharpen cognitive function and prevent dementia. This study used a case study method with nine elderly respondents at the Jolotundho guest house, Tresna Werdha Yogyakarta Social Service Center. The elderly actively engaged in the game, expressed happiness, and enthusiastically shared memories associated with the objects in the images. They recalled past experiences and demonstrated an improved ability to remember and describe objects, indicating enhanced cognitive function. The results suggest that PAKARNOS is an effective educational and recreational tool to improve memory, reduce dementia risk, and provide meaningful activities for the elderly.